Supply Chain Coordination under Uncertainty - Choi, Tsan-Ming; Cheng, T.C. Edwin (International Handbooks on Information Systems, 2011)
Channel coordination is a core subject of supply chain management. Over the past decade, much research effort has been devoted to exploring the detailed mechanisms for achieving supply chain coordination under uncertainty, generating many fruitful analytical and empirical results. Despite the abundance of research results, there is an absence of a comprehensive reference source that provides state-of-the-art findings on both theoretical and applied research on the subject. In addition, with the advance of knowledge and technologies, many new topics on supply chain coordination under uncertainty have appeared in recent years. This handbook extensively examines supply chain coordination challenges with a focal point on discovering innovative measures that can help tackle the existing and emerging challenges. The book is organized into five parts, which include chapters on innovative analytical models for coordination, channel power and bargaining, technological advancements and applications, empirical analysis, cases studies and review. This handbook provides new empirical and analytical results with precious insights, which will not only help supply chain agents to understand more about the latest measures for supply chain coordination under uncertainty, but also help practitioners and researchers to know how to improve supply chain performance based on innovative methods.